Prognostic impact of age on outcomes of hepatic decompensation in patients with compensated cirrhosis (CHESS2102): an international, multicenter cohort study - Shanghao Liu; Jia Li; Yujun Wong; Hyung Joon Yim; Masashi Hirooka; Hirayuki Enomoto; Qing Xie; Erhei Dai; Amr Shaaban Hanafy; Zhujun Cao; Lili Zhao; Kok Ban Teh; et al. (MedComm, 2024)
Abstract Baveno VII criteria (B7C) and Baveno VI criteria (B6C) have been widely used to estimate the risk of hepatic decompensation. However, the impact of age on these criteria warrants further investigation. The international, multicenter cohort study included 1138 patients with compensated cirrhosis (median follow‐up of 40.6 months), aiming to evaluate the value of age in predicting hepatic decompensation. We identified age as an independent predictor of hepatic decompensation, with 60 years determined as the optimal cut‐off value. The occurrence of decompensation was 18.7% and 6.7% in the older (age ≥60 years) and younger (age <60 years) groups, respectively (p < 0.001). We subsequently integrated age into the existing Baveno criteria. In patients not meeting Baveno criteria (defined as not meeting B6C or B7C), the older group exhibited a significantly elevated risk of decompensation compared to the younger group (p < 0.05). However, no significant difference was observed between the older and younger groups in patients meeting Baveno criteria (p > 0.05). In conclusion, our study demonstrated that integrating age into the Baveno criteria could enhance the assessment of hepatic decompensation. Age should be considered before discharging patients with compensated cirrhosis from the surveillance of hepatic decompensation.